Ponto de Acesso Vol. 8, n. 1 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Ponto de Acesso Vol. 8, n. 1 (2014) Link de acesso ao númerohttp://www.portalseer.ufba.br/index.php/revistaici/issue/view/913